2015
DOI: 10.3109/07420528.2015.1014094
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of dizziness and vertigo in a tropical region

Abstract: Vertigo and dizziness are among the most common medical complaints in the emergency room, and are associated with a considerable personal and health care burden. Scarce and conflicting reports indicate those symptoms may present a seasonal distribution. This study aimed at investigating the existence of a seasonal distribution of vertigo/dizziness in a tropical region, and the correlations of these findings with climatic variables. The charts of all patients consecutively admitted between 2009 and 2012 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
3
8
0
2
Order By: Relevance
“…In addition, the results of this study indicated that there were 1.56 times (95% CI 1.23, 1.96) greater risk for an episode on the days with low pressure and high humidity compared to days with high pressure and low humidity. Likewise this study, Pereira et al 9 stated in their study that there was a negative correlation between atmospheric pressure and not only patients with Meniere's disease but also patients applying to the emergency room with complaints of vertigo. The result obtained related to changes in pressure in the present study were similar to those of the study by Pereira et al, 9 .…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In addition, the results of this study indicated that there were 1.56 times (95% CI 1.23, 1.96) greater risk for an episode on the days with low pressure and high humidity compared to days with high pressure and low humidity. Likewise this study, Pereira et al 9 stated in their study that there was a negative correlation between atmospheric pressure and not only patients with Meniere's disease but also patients applying to the emergency room with complaints of vertigo. The result obtained related to changes in pressure in the present study were similar to those of the study by Pereira et al, 9 .…”
Section: Discussionsupporting
confidence: 55%
“…Various studies reported that there might be the unequal seasonal distribution for vertigo, Meniere's disease, and paroxysmal vestibular vertigo; however, they were monitored more frequently in spring and winter months 7,13,14 . Pereira et al, 9 investigated seasonal distribution of cases with vertigo and dizziness in a tropical region and the correlation to climatic variables in their study and they revealed that there was a significant correlation between vertigo and dizziness and seasons. The present study concluded that vertigo was rather observed in winter and late spring, showed a negative correlation with humidity (r = -0.374; p = 0.013) and precipitation (r = -0.334; p = 0.020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The humidity is the highest and the atmospheric pressure is the lowest in summer; this decreases and increases, respectively, in the order of autumn, spring, and winter. A previous study reported that high humidity and lower atmospheric pressure are associated with higher odds of an attack and higher levels of vertigo, tinnitus, and aural fullness in patients with MD [Pereira et al, 2015;Schmidt et al, 2017] A characteristic feature often observed in MD is endolymphatic hydrops, which is a condition of excessive accumulation of endolymph in the cochlea [Hallpike and Cairns, 1938] The change in atmospheric pressure may influence endolymphatic hydrops via the middle ear [Schmidt et al, 2017]. It is known that if the air is more humid, the speed of sound increases, and the effect of humidity on the speed of sound is slightly greater at lower air pressures [Davis and Ralph, 1987].…”
Section: Discussionmentioning
confidence: 95%
“…Pereira et al [ 36 ] examined the seasonality of the incidence of cases presenting to a large emergency department with dizziness and vertigo in the tropical region of southern Brazil. For the symptom “vertigo” (which would rather correspond to our definition of MD attacks than “dizziness”), they found a significant seasonality pattern, with a peak in late winter.…”
Section: Discussionmentioning
confidence: 99%